Intrinsic Motivation in The Development of Motivational Interviewing Method for Compliance Programs in Hypertension Patients - Efitra Efitra; Lola Felnanda Amri; Yessi Fadriyanti; Evino Sugriarta (Yayasan Ahmad Mansyur Nasirah, 2026)
Hypertension is a non-communicable disease and a major contributor to global mortality, including in Indonesia. Uncontrolled hypertension over a prolonged period can lead to arterial damage and adversely affect organs supplied by these blood vessels. Increased blood pressure places excessive workload on the heart, impairing its ability to pump blood effectively. Furthermore, hypertension increases the risk of stroke, kidney failure, hypertensive retinopathy, and even blindness. Efforts to control blood pressure require not only medical management but also strong internal motivation from patients. This study aimed to explore the internal motivation of hypertensive patients in controlling blood pressure through “OBEY” behavior. This study employed a qualitative research design using Focus Group Discussion (FGD). The participants were patients diagnosed with hypertension. The analysis identified key themes related to the implementation of “OBEY” behavior among hypertensive patients. The findings of this study are expected to serve as a basis for developing a Motivational Interviewing module tailored for hypertension patients to improve adherence and blood pressure control.